IMPLEMENTASI PENANGANAN TINDAKAN KEKERASAN DALAM RUMAH TANGGA TERHADAPPEREMPUAN BERDASARKAN UNDANG-UNDANG NOMOR 3 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Dwi Putri Melati (PRANATA HUKUM, 2017)
Some of the problems we encounter in married life, and often the occurrence of violence between husband and wife, then the subject matter in this paper about the handling of the law on acts of domestic violence experienced by women under the law no. 3 of 2004 on the Elimination of Domestic Violence. Problem approach using normative juridical approach (legal research). The victim can make a complaint on the violent acts committed by the victim's husband / wife, because in the complaint the authorities will not process the action without any complaints from the victim, it can also be revoked by the victim which in fact is the husband / wife of the perpetrator. Law enforcers must be firm in handling cases of domestic violence, Doers of Domestic Violence really should be processed fairly, victims of domestic violence should get legal protection